The Functional Analysis of Gender Equality in the Islamic Law Perspective - Putra, Adji Pratama; Ma'arif, Khoirul; Yahya, Mad; Pangestu, Fachri Hamzah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The causative factors of the gender equality problem include misunderstanding social roles between men and women as a result of an incomplete understanding of Islamic law. This misunderstanding of gender equality results in unequal conceptions placing the positions of men and women in society.This article aims to the primary data sources in this article are the Qur'an text which outlines the gender equality issues in the Islamic law perspective. This article is a qualitative study with a normative juridical approach by describing and analyzing the concept of gender in the Qur'an and fiqh. The results of this study explain that Islam teaches equality between humans, both men and women. At least there are five principles of gender equality in Islam, men and women are both servants of Allah Swt, men and women are both caliphs of Allah, men and women both accept the primordial covenant, men (Adam) and women (Hawa) are both actively involved in the events of the cosmic creation, and men and women have the same potential for achievement. The Qur'an emphasizes the equal status of men and women in terms of fundamental rights as their existence as human and divine beings.